Напрямки ефективної організації постачання сільськогосподарських вантажів - Шраменко, Наталя; Шраменко, Владислав (ТзОВ «Галицька видавнича спілка», 2021)
It is determined that agricultural goods have a significant share in the overall structure of transported goods of each mode of transport. It is determined that road transport occupies the largest share in the total volume of agricultural cargo transportation. The priority directions of formation of supply chains of agricultural cargoes are allocated.
Directions for effective organization of agricultural cargo supplies
Keywords: 656.025